2021
DOI: 10.1080/09553002.2021.1928782
|View full text |Cite
|
Sign up to set email alerts
|

RENEB Inter-Laboratory comparison 2017: limits and pitfalls of ILCs

Abstract: Purpose: In case of a mass-casualty radiological event, there would be a need for networking to overcome surge limitations and to quickly obtain homogeneous results (reported aberration frequencies or estimated doses) among biodosimetry laboratories. These results must be consistent within such network. Inter-laboratory comparisons (ILCs) are widely accepted to achieve this homogeneity. At the European level, a great effort has been made to harmonize biological dosimetry laboratories, notably during the MULTIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Similar to recent RENEB ILCs ( 17, 18, 23 ), heterogeneity was observed with regard to the calibration curves used by the participants. This strongly suggests that each laboratory should use its own calibration curve and regularly perform intra-laboratory quality checks to ensure if the scoring does still agree with the used calibration curve, especially when there are changes in the staff of the laboratory.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Similar to recent RENEB ILCs ( 17, 18, 23 ), heterogeneity was observed with regard to the calibration curves used by the participants. This strongly suggests that each laboratory should use its own calibration curve and regularly perform intra-laboratory quality checks to ensure if the scoring does still agree with the used calibration curve, especially when there are changes in the staff of the laboratory.…”
Section: Discussionsupporting
confidence: 55%
“…One recent publication from Saudi-Arabia compared dose effect curves based on a 320 kVp X-ray source between 10 adult donors and suggested that the differences between individuals can be neglected ( 49 ). Moreover, several exercises performed with variable donors have shown that doses can be successfully recovered based on the DCA ( 17, 18, 41, 50, 51 ). Nevertheless, it cannot be fully excluded that individual variations contributed to the observed bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In biodosimetry, many exercises of different sizes have been organized (Beinke et al, 2013;Rothkamm et al, 2013;Wilkins et al, 2015;Oestreicher et al, 2017;Pan et al, 2019;Port et al, 2019;Endesfelder et al, 2021;Gregoire et al, 2021). One such exercise was recently carried out by RENEB in partnership with EURADOS Working Group 10.…”
Section: Lessons From Biodosimetry and Covid-19: Interlaboratory Comp...mentioning
confidence: 99%
“…Within the RENEB network, regular inter-laboratory comparison exercises have been organized for harmonization and training as well as to maintain the preparedness for large-scale emergency situations, using a broad variety of biodosimetric assays (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%